ANALISA KELAYAKAN USAHA PRODUKSI KOPI DARI BUAH MANGROVE (Avicennia marina) DI DESA LABUHAN, BANGKALAN, JAWA TIMUR - Sholeh, Moh (Universitas Muhammadiyah Gresik, 2025)
The purpose of this study was to analyze the business feasibility of the Mangrove Coffee Production (Avicennia marina) in Labuhan Village, Sepulu District, Bangkalan Regency, Madura, East Java Province. The method used in this study is descriptive analysis with qualitative and quantitative approaches. The mangrove coffee production process in Labuhan Village is carried out using a semi-modern system because it still uses manual tools such as peeling and slicing fruit which still uses a knife, roasting mangrove fruit which still uses a pan made of clay and a stove. The production process includes washing, peeling and slicing, grinding, and packaging. Based on the feasibility analysis obtained, the mangrove coffee production business in Labuhan Village is categorized as feasible, has good prospects, and can be developed on a large scale. The results of the analysis show that NPV> 1, IRR> discount factor, B / C Ratio> 1, and Payback Period <5 years.